Influence Of Epoxy Viscosity And Gold Wire Size On Led Encapsulation Process - Goh, Wei Shing (Universiti Sains Malaysia, 2021)
There are a few issues experienced in high-power LED applications that severely influence the reliability of the LEDs. One of the most problems of the LED failure is wire deformation or wire sweep during the encapsulation process that can indirectly affect the LED life expectancy. The goal of this study was to examine the encapsulation process of the LED and to correlate the impact of viscosity of the epoxy molding compound (EMC) and the gold wire bonding diameter during the LED encapsulation process. The advanced simulation tool, ANSYS Fluent is utilized to complete an investigation on the fluid-structure interaction (FSI) phenomena between the gold wire bonding and the EMC. The FSI modelling was used to measure the amount of stresses indirectly applied to the gold wire bonding during the encapsulation process. Besides, the volume of the EMC being dispense onto the LED substrate will be simulated by utilizing the volume of fluid (VOF) strategy and user-defined function (UDF) in the ANSYS Fluent. The simulation can be conducted repeatedly by changing the viscosity of the EMC (0.248 kg/m.s, 0.448 kg/m.s, and 0.648 kg/m.s) and the gold wire diameter (0.025mm, 0.028mm, 0.030mm, 0.032mm, and 0.035mm). Parameters such as injection speed, injection time, and inlet contact angle are fixed in this study. An experiment test was done to approve the final structure of the EMC results obtained from the simulation under similar setup conditions. The results demonstrated that the wire deformation, stress and strain distributed on the wire bonding increased with increasing viscosity of the EMC. The high viscosity of the EMC would yield higher deformation, stress and strain distributions of the gold wire bonding. The results also showed that the smaller the diameter of the gold wire, the larger the stress and strain distributions when the same type of viscosity of the EMC is applied.